COMBUSTION MODEL FOR SPARK IGNITION ENGINES OPERATING ON GASOLINE-ETHANOL BLENDS - Mantilla, J. M.; Garzón, D. A.; Galeano, C. H. (Revista de Engenharia Térmica, 2010)
This article presents a phenomenological combustion model using turbulent flame propagation theory developed by Keck and coworkers, 1974. The model was adapted to work with gasoline-ethanol blends, following correlations presented by Bayraktar,2005. New sub-models were introduced for intake valve velocity and combustion efficiency. These allow simulating the effect of compression ratio, spark timing and fuel change. Results show good agreement with the ones in the original work as well as with experimental results in a Cooperative Fuels Research (CFR) engine.